Plasma Heme Scavengers Alpha-1-Microglobulin and Hemopexin as Biomarkers in High-Risk Pregnancies - Kalapotharakos, Grigorios; Murtoniemi, Katja; Åkerström, Bo; Hämäläinen, Esa; Kajantie, Eero; Räikkönen, Katri; Villa, Pia; Laivuori, Hannele; Hansson, Stefan R. (Frontiers in Physiology, 2019)
Women with established pre-eclampsia (PE) have increased plasma concentration of free fetal hemoglobin. Furthermore, women with PE and SGA or growth restricted fetus have a distinct cardiovascular phenotype characterized by lower cardiac output and higher peripheral vascular resistance. We measured two hemoglobin scavenger system proteins, hemopexin (Hpx) and alpha-1-microglobulin (A1M) in maternal plasma using enzyme-linked immunosorbent assay during the late second trimester of pregnancy in women with high and low risk of developing PE. In total 142 women were included in nested case-control study: 42 women diagnosed with PE and 100 controls (49 randomly selected high-risk and 51 low-risk controls). The concentration of plasma A1M in high-risk controls was higher compared to low-risk controls. The plasma level of Hpx in women with PE who gave birth to small for gestational age (SGA) infant was lower compared to women with PE who gave birth to non-SGA infant. Women with severe PE had higher plasma A1M levels compared to women with non-severe PE. In conclusion, the concentration of plasma A1M is increased in the late second trimester in high-risk controls, suggesting activation of endogenous protective system against oxidative stress. The association of low plasma Hpx concentration with PE complicated by SGA suggests that the heme scavenger system is activated in preeclamptic cases characterized by low cardiac output.